Ethical challenges in ESG reporting: comparing Malaysia, Thailand, and Indonesia - Mior Badrul Munir, Mai Farhana; Abdullah, Azrul; Mohd Noor, Marjan (Faculty of Accountancy, 2024)
Environmental, social, and governance (ESG) is increasingly important in modern business as it reflects a company's commitment to sustainability and social responsibility. ESG is an important framework that assists stakeholders in understanding how companies manage their risks and opportunities related to ESG criteria as shown in Figure l. ESG issues have attracted widespread attention from the practical and academic communities (Li et al., 2021)and companies have disclosed various kinds of ESG reporting to satisfy the stakeholders' expectations (Lokuwaduge & Heenetigala, 2017)